The Cults of St. Anastasia and St. Chrysogonus in Medieval Zadar: Reflections of Internal Urban Conflict? - Vedriš, Trpimir (2004)
The presentation inquires the shift of the two principal patron saints of Zadar between 12^th and 14^th centuries. The central topic is the emergence of the commune and fragmentation of the spiritual and secular authority, when the urban monastery of St. Chrysogonus came to play a major political role and its abbots oppose the authority of the archbishops of Zadar and actively participate in the resistance to Venice. Whileit seems that the cult of St. Anastasia, venerated in the city cathedral, was more important in the early Middle Ages, the cult St. Chrysogonus came to play an important role in city politics only with the growing power of the monastery in the High Middle Ages. Venerated in the early period as a monk, Chrysogonus came to be represented as a knight, whose image as a charging horseman came to symbolise the pride and self-confidence of the commune of Zadar. With the upgrading of the bishopric to the archbishopric level in the mid-twelfth century the position came under the strong influence of the Venice, leading eventually to the introduction of Venetian bishops in the following centuries. At the same time, the monastery developed strong relations with the Croatian and Hungarian court, becoming the political power known as the "kings party" in Zadar. The paper shows how the cults of St. Anastasia and of St. Chrysogonus reflected these tensions, and how the social and political circumstances led to the replacement of the city's principal patron saint St. Anastasia, and established St. Chrysogonus as the principal patron of the commune.